Detection of food-borne viruses on ready-to-eat meat products and meat processing establishments in Cyprus - Markantonis, Nikolas (Department of Agricultural Science, Biotechnology and Food Science, Faculty of Geotechnical Science and Environmental Managment, Cyprus University of Technology, 2016)
Food-borne viruses are able to contaminate and persist on food, therefore causing disease and in some occasions even death among the exposed population. The major food-borne viruses are NoV, RV, HAV and HEV, causing acute gastroenteritis (NoV,RV) and acute hepatitis (HAV,HEV). The economic burden of food-borne viral infections is also very important for the food industry, because contamination will result to withdrawal and destruction of products. The involvement of food products in large outbreaks of acute gastroenteritis and hepatitis has let scientists around the world to categorize food stuffs with higher risk. Vegetables, fruits, shellfish and ready-to-eat products have been involved in several food-borne outbreaks of acute hepatitis and gastroenteritis. Viruses found on such products, which can be eaten raw or partially cooked, can remain active until consumption, therefore are in higher risk. Ready-to-eat meat products such as ham, salami and bacon can be contaminated with viruses, by infected handlers during the process of packaging. In Cyprus, no study has attempted to record the prevalence of food-borne viruses in animal origin products and establishments yet. Therefore, in this pilot study, ready-to-eat meat products and establishments of two meat-processing plants in Cyprus have been analysed for the presence of NoV, RV, HAV and HEV, using RT-qPCR. The meat products analysed were ham, bacon, salami, hiromeri and lountza. Additionally, swabs from the two establishments were also analysed, including processing equipment (slicing machine, trimming machine, scales), toilet handles and workers hands. The slicer machine and the hand of a handler from plant B were found to be positive to NoV. Contamination of ready-to-eat meat products just before packaging can result to public health threats, since the products usually are consumed raw without any further processing. The results of this study disclose the dangers for public health by food-borne viruses and set the foundations for further examination of this issue.
Keywords: Food industry; Food-borne viruses